Sociodemographic and Clinical Factors Associated With Nirsevimab Receipt Among Children Aged Younger Than 20 Months in the New Vaccine Surveillance Network in 2023 to 2025 - Zheyi Teoh; Ayzsa Tannis; Erin Sullivan; Julie A. Boom; Natasha Halasa; Marian G. Michaels; Daniel C. Payne; Leila C. Sahni; Jennifer Schuster; Rangaraj Selvarangan; Mary Allen Staat; Laura S. Stewart; et al. (Hospital Pediatrics, 2026)
OBJECTIVES We aim to evaluate the association of sociodemographic and clinical factors with nirsevimab receipt among children with medically attended acute respiratory illness (ARI) across multiple seasons and beyond birth hospitalization. PATIENTS AND METHODS We included nirsevimab-eligible children aged younger than 8 months and 8 to 19 months with ARI enrolled in the New Vaccine Surveillance Network during the 2023 to 2024 and 2024 to 2025 respiratory syncytial virus (RSV) seasons (October 1 to March 31). A mixed-effects logistic regression model was used to evaluate the association between sociodemographic and clinical factors with the likelihood of nirsevimab receipt among enrolled children aged younger than 8 months. RESULTS Of the 2151 nirsevimab-eligible children with ARI enrolled in the 2023 to 2024 RSV season and 1819 in the 2024 to 2025 RSV season, 96% were aged younger than 8 months and in their first RSV season. Fourteen percent and 36% of eligible children aged younger than 8 months received nirsevimab in the 2023 to 2024 and 2024 to 2025 seasons, respectively. Among infants aged younger than 8 months, those born during the RSV season and those with an underlying medical condition were more likely to receive nirsevimab in both RSV seasons; infant female sex and maternal education were also associated with nirsevimab receipt during 2023 to 2024 but not 2024 to 2025. CONCLUSION Most nirsevimab-eligible children with medically attended ARI in this analysis did not receive nirsevimab during the first 2 seasons of nirsevimab availability. Factors such as birth before the RSV season were associated with a decreased likelihood of nirsevimab receipt, emphasizing the need for tailored interventions following birth hospitalization to increase nirsevimab uptake for this group of children.